Akibat Hukum Pembatalan Pelaksanaan Perkawinan Secara Sepihak - Bairatnissa, Zulvira Zalleh; Latupono, Barzah; Fataruba, Sabri (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Marriage must go through a legal process and be recognized by both the community and the state.Purposes of the Research:the purpose of compiling this writing for all people who study law in the civil field, especially those related to the factors causing annulment and legal consequences of unilateral annulment of marriageMethods of the Research: The research method used is normative juridical, with a statutory and conceptual approach. The sources of legal materials used are primary, secondary, and tertiary legal materials. The technique of gathering legal materials carried out in this study was library research, then it was analyzed qualitatively.Results  of the Research: The laws and regulations regarding marriage do not regulate at all the legal consequences related to the unilateral cancellation of marriage (marriage) after the proposal and engagement, so people are so easy to annul it unilaterally to the detriment of the other party.However, if referring to the jurisdiction of the Supreme Court Number 3191 K/Pdt/1984 dated December 12, 1985, then the unilateral annulment of marriage (marriage) after the proposal and engagement is a violation of the norms of decency and propriety in society, and is an act against the law,where this jurisprudence is then used as the basis of legal consideration of the Supreme Court judge in Decision Number: 1644 K/Pdt/2020. Namely the decision on the unilateral annulment of marriage (marriage) after the proposal and engagement made by Agus Suyitno to his partner Sri Subur Lestari.